Cardiac magnetic resonance imaging and computed tomography in ischemic cardiomyopathy: an update - Assunção,Fernanda Boldrini (2016)
Abstract Ischemic cardiomyopathy is one of the major health problems worldwide, representing a significant part of mortality in the general population nowadays. Cardiac magnetic resonance imaging (CMRI) and cardiac computed tomography (CCT) are noninvasive imaging methods that serve as useful tools in the diagnosis of coronary artery disease and may also help in screening individuals with risk factors for developing this illness. Technological developments of CMRI and CCT have contributed to the rise of several clinical indications of these imaging methods complementarily to other investigation methods, particularly in cases where they are inconclusive. In terms of accuracy, CMRI and CCT are similar to the other imaging methods, with few absolute contraindications and minimal risks of adverse side-effects. This fact strengthens these methods as powerful and safe tools in the management of patients. The present study is aimed at describing the role played by CMRI and CCT in the diagnosis of ischemic cardiomyopathies.